Departmental Leadership: Navigating Productive Tension While in a Paradoxical Role - Caron, Rosemary M. (Frontiers in Education, 2019)
The landscape of higher education is dynamic and calls for faculty and academic administrators to not only prepare those entering the workforce with current skills, knowledge, and values but to do so in an environment that is resourceful with the tools, and personnel necessary to educate the citizenry. A critical component in achieving this noble mission is the role of the Department Chair, who spans both the academic and administrative environments. The Department Chair, whether at a public or private institution must serve multiple masters which include, senior academic administrators, departmental faculty, staff, students, parents, alumni, community partners, and donors. The challenges that arise while in this role are many, for example, budgetary, personnel, and academic program accreditation/certification. Successes also do occur as evidenced by enrollment and graduation rates, and sincere appreciation from those we have taught. The Department Chair role is essential and deserves to possess the authority necessary to make decisions that are in the best interest of students, faculty, and the academic programs offered. The purpose of this perspective is to offer recommendations, grounded in experience, that may assist the Department Chair in navigating productive tension that can arise while working in this role that is often paradoxical at times.